Alterations in the Effects of Warfarin in Dogs by Halofenate - Weintraub, Michael; Griner, Paul F (Thrombosis and Haemostasis, 1975)
The interaction between warfarin and the new lipid lowering agent halofenate (MK 185) [2 - acetamidoethyl (p-chlorophenyl) (m-trifluoromethylphenoxy) acetate] was studied in dogs in both short- and long-term experiments. Our data suggest that halofenate potentiates the anticoagulant effect of warfarin by increasing the degradation of prothrombin (factor II) (Kdeg on placebo = 211 ± 32 × 10−4 × Hr−1 mean ± SEM; on halofenate = 268 ± 39 × 10−4 × Hr−1 mean ± SEM; P < 0.01). However, a concomitant increase in factor II synthesis of 34% results in resistance to warfarin’s effect if halofenate is administered prior to warfarin. The mean prothrombin time of 4 dogs on 2 mg of warfarin following halofenate pretreatment for 8 weeks was 74.8% ± 17.3 (SE) of the anticoagulated control dog. On 2 mg of warfarin alone, it was 133.7% ± 42.0 (P < 0.001). Cessation of halofenate from combined therapy results in a delayed augmentation of warfarin effect. These data suggest that the nature of the interaction between warfarin and drugs such as halofenate which alter the kinetics of prothrombin may depend on the sequence of administration.